Kesahan dan kebolehpercayaan dalam parameter kinematik dayungan ergometer kayak (IR) - Benderi Dasril (2008)
The purpose of this study is to determine the reliability and validity of Dansprint Pro K-1 kayak ergometer in kinematic of paddling parameter. Sixteen (16) UPSI kayak atheletes and sixteen national level athletes involve in this study. Prerecorded data from two (2) high speed camera (Panasonic WV-CP 450/G) which were obtained from two separated test Protocol X (reliability test) and Protocol Y (validity test) were analized using Peak Motus 4.0 Motion Analysis System software. This software are able to analized and measured 3 Dimensional kinematic parameters. Pearson Product Moment correlation statistic are use to get correlation coefficient value and level of significant of relationship between paddling kinematic variables from each test. Results from reliabilty test showed a high correlation coefficient value and significant in elbow angle at catch phase (r = 0.74, p<0.05), vertical (r = 0.97, p<0.05) and exit (r = 0.78, p<0.05) paddling kinematic parameters. This result proof that this kayak ergometer is reliable in measuring that kinematic variables. Twelve (12) from sixteen (16) variables analyze showed a positive and significant relationship (r = 0.81 to r = 1.00 with significant level p